Digital Security Research Based on Blockchain and Zero Trust : A Bibliometric Analysis (2018–2025) - Farrel Carasiola; Rakhmadi Irfansyah Putra (ISB Atma Luhur, 2026)
Research integrating blockchain and Zero Trust for digital security is growing rapidly, yet the field remains fragmented and lacks a clear longitudinal mapping of its intellectual and thematic structure. This study applies a Scopus-based bibliometric analysis of 43 publications from 2018–2025 to examine publication growth, collaboration patterns, and knowledge structures using Biblioshiny (bibliometrix). The results show accelerated scientific growth (49.89% annual growth rate) and substantial impact (59.16 citations per document), with an international collaboration rate of 41.86%. Keyword and thematic analyses indicate that blockchain, cybersecurity, and authentication dominate the research landscape, positioning blockchain and cybersecurity as motor themes, while Zero Trust Security emerges as a developing niche theme. This study contributes a consolidated longitudinal map of research fronts, collaboration dynamics, and theme positioning, providing actionable insights for designing decentralized and adaptive security architectures and guiding future research directions in blockchain–Zero Trust digital security.